Investigation new positions for catalytic activity of Chaetomium thermophilum and Ceriporiopsis subvermispora formate dehydrogenases - Kocdemir, Kubra; Sen, Fatma; Wedajo, Yasin Adem; Bilgici, Muazzez Cagla; Bayram, Mustafa; Selcuk, Ilke; Yilmazer, Berin (Taylor & Francis Ltd, 2021)
NAD(+)-dependent formate dehydrogenases (FDHs, E.C 1.2.1.2) catalyse the reversible reaction of CO2 to formate ion (HCOO-) and reduces NAD(+) molecule to NADH. Previously described FDHs from Chaetomium thermophilum (CtFDH) and Ceriporiopsis subvermispora (CsFDH) are active against formate and HCO3 (-). In this study, we examined the functional effects of active site mutations in Ct and Cs NAD(+)-dependent FDHs. The residues Ile94, Asn120, Val310, His312 at CtFDH and Asn312, Val313, Val331 at CsFDH are located in the active site. The effects of amino acid changes on catalytic properties and thermal stability of CtFDH and CsFDH revealed some interesting results compared with structurally equivalent positions that have been studied in the literature. The strongest effect was observed in CsFDH Val313Pro against HCO3 (-). The K-M value of the CsFDH Val313 enzyme for HCO3 (-) substrate dramatically decreased, and enzyme activity increased. In CtFDH mutants, all enzymes except Val310Asn showed an increased k(cat) value when K-M values increase. Analyses of results of mutant CtFDHs and CsFDHs give some promising results for CO2 reduction as compared to the literature. Structural analyses of the substrate-binding site were done by homology modelling.
Keywords: Protein engineering; NAD(+)-dependent formate dehydrogenase; CO2 reduction; site-directed mutagenesis; molecular modelling